REFLEXÕES HISTÓRICAS DA FORMAÇÃO DO CONCEITO DE ESTADO: CONSIDERAÇÕES CRÍTICAS ÀS PRÁTICAS DO ESTADO LEGALISTA. (Reflection and Critique Law Magazine, 2025)
The current Brazilian scenario is marked economically by the process of globalization and all the elements that involve it, as well as by the advancement of Neoliberal policies that serve as rhetoric for power managers to implement the minimum for social policies and at the same time the maximum for Capital and its holders. In this scenario, it is necessary to (de)construct theoretically and axiologically the concept of State, seeking to demonstrate the historical period of its birth and the conditions that allowed this to happen, as well as pointing out some criticisms of the practices of the Legalist State disguised as a State. Democrat of Law who daily succumbs to rights gradually acquired by the Brazilian population.